2015
DOI: 10.1002/pssb.201552418
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond spin lifetimes in bottom-up fabricated bilayer graphene spin-valves with atomic layer deposited Al2O3 spin injection and detection barriers

Abstract: We present spin transport studies on bi‐ and trilayer graphene non‐local spin‐valves which have been fabricated by a bottom‐up fabrication method. By this technique, spin injection electrodes are first deposited onto Si++/SiO2 substrates with subsequent mechanical transfer of a graphene/hBN heterostructure. We showed previously that this technique allows for nanosecond spin lifetimes at room temperature combined with carrier mobilities which exceed 20,000thinmathspacenormalcm2(Vsfalse)−1. Despite strongly enh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…In this case, the actual spin lifetime is underestimated by more than a factor of two. How- ever, the increase in spin lifetime for low gate voltages is similar to what is observed in experiments [10][11][12][17][18][19][20][21][22][23][24] . But the relative change in amplitude in the simulation is significantly smaller.…”
Section: Spatially-varying Spin Transport Parametersupporting
confidence: 84%
See 2 more Smart Citations
“…In this case, the actual spin lifetime is underestimated by more than a factor of two. How- ever, the increase in spin lifetime for low gate voltages is similar to what is observed in experiments [10][11][12][17][18][19][20][21][22][23][24] . But the relative change in amplitude in the simulation is significantly smaller.…”
Section: Spatially-varying Spin Transport Parametersupporting
confidence: 84%
“…A sketch of the device structure is shown in Figure 1a. The electrode configuration is comparable to the layout used in some of our previous spin transport experiments 10,11,24 . The electrode width for the outer contacts reference electrodes is W = 1 µm and is alternating between W = 600 nm and W = 300 nm for the inner electrodes.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] With this procedure we are able to reproducibly build devices showing nanosecond spin lifetimes at room temperature even in case of short transport channel lengths of 2 − 3.5 µm. [36,37] In this Letter, we present spin transport studied in bottom-up fabricated graphene devices that pushes the measured room temperature spin lifetimes in single layer graphene by a factor of 6 from around 2 ns to 12.6 ns yielding spin diffusion lengths of 30.5 µm. These values exceeds current models for contact-induced spin dephasing ruling out spin absorption as the the dominant source of spin dephasing.…”
mentioning
confidence: 84%
“…4,10 Among all of the carbon based structures, the hexagonal arrangement of carbon atoms in two dimensions, graphene, is particularly intriguing. The low efficiency of the spin relaxation of up to a nanosecond, [11][12][13] the scalability of the total spin, and graphene's stability up to room temperature make graphene based materials excellent candidates for spintronic devices. [14][15][16][17] Furthermore, it has been shown that magnetic graphene nanoakes (GNFs) have the potential for an extremely long spin relaxation and decoherence time, with weak coupling between electron spins, and long-range magnetic order.…”
Section: Introductionmentioning
confidence: 99%